(untitled) (Ukrainian Journal of Ophthalmology, 2025)
Homocystinuria is an inborn error of metabolism caused by cystathionine b-synthetase deficiency, with autosomal recessive inheritance. The clinical picture is characterized by skeletal changes, mental deficit, lens subluxation, and a tendency to thromboembolic phenomena. The case of a 35-year-old male patient with a marfanoid habit, eviscerated right eye, and abrupt loss of visual acuity of the left eye is reported, showing lens luxation; the determination of plasma homocysteine was reported elevated 285μmol / L (5-16μmol / L), confirming the diagnosis of homocystinuria. The management is multidisciplinary, the ophthalmological treatment required vitrectomy.